2012
DOI: 10.1080/19768354.2011.620173
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and reproductive aspects of the pandalid shrimp,Pandalus eous,in the deep sea of the East Sea, Korea

Abstract: The objective of the study was to investigate if reproductive characteristics of Pandalus eous affect the depth distribution in the East Sea of Korea. P. eous was found at depths of 500Á900 m in the East Sea of Korea, with the highest percentage occurrence (34%) at 500 m. A negative correlation was observed between the number of individuals and the depth. The overall sex ratio also turned out to be significantly correlated with depth. On average, the larger individuals (bigger than 26.37 cm), which included tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…We found that crustaceans were the dominant species in summer and autumn in this study because of the behavior and life history of crustacean prey (Xue et al 2005;Blasina et al 2010). P. eous used as prey mainly migrate to inshore (< 50 m) for the larval hatch during late winter and early spring (Park et al 2012;Richards 2012). The density of crustaceans increases as the hatched crustaceans recruit in summer.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We found that crustaceans were the dominant species in summer and autumn in this study because of the behavior and life history of crustacean prey (Xue et al 2005;Blasina et al 2010). P. eous used as prey mainly migrate to inshore (< 50 m) for the larval hatch during late winter and early spring (Park et al 2012;Richards 2012). The density of crustaceans increases as the hatched crustaceans recruit in summer.…”
Section: Discussionmentioning
confidence: 68%
“…The density of crustaceans increases as the hatched crustaceans recruit in summer. Also, P. eous can be captured more than other invertebrates because P. eous inhabit in various water depths up to 600 m deep (Park et al 2012). Therefore, larger individuals of Z. faber inhabit in deeper depths and can consume crustaceans abundantly.…”
Section: Discussionmentioning
confidence: 99%